Anggaru Klawu: Metafora Fauna Endemik Indonesia Owa Jawa Dalam Penciptaan Busana Dengan Art Of Beat Style - Mitariani -; I Nyoman Artayasa; Nyoman Dewi Pebryani (Style : Journal of Fashion Design, 2021)
Indonesia is a country which has a diversity of flora and fauna. One of the endemic faunas of Indonesia is the Javan Gibbon. The Javan Gibbon (Hylobates Moloch) is a species of small ape without a tail with long arms, gray hair, and a distinctive voice. The Javan gibbon is an animal that is startining become endangered animal and almost extinct so that the IUCN Redlist has categorized as an  "endangered" or threatened extinct. Javan Gibbons are the source of ideas for creating ready-to-wear, ready-to-wear deluxe and haute couture clothing which are implemented with metaphorical theory based on selected keywords, namely diurnal, arboreal, monogamous, territorial, sound, long sleeves, attracting attention and art of beat. The foundation of this fashion creation is using the method of. Tjok Istri Ratna Cora Sudharsana, namely Frangipani. “FRANGIPANI, The Secret Steps of Art Fashion” which consists of ten stages in the process of crafty fashion designs. The result of this creation is expected to be able to introduce to many people that Indonesia has the Javan Gibbon as an endemic animal of Indonesia that must be preserved in order that it does not become extinct.